Natural disasters, mitigation and household welfare in Indonesia: Evidence from a large-scale longitudinal survey - Teguh Dartanto (Cogent Economics & Finance, 2022)
Households around the world as well as in Indonesia have become exposed to a wider variety of vulnerabilities and risks in recent years due to an increase in the intensity and scope of natural disasters. This study aims to comprehensively examine the impact of natural disasters on Indonesian household welfare (consumption and poverty) using the Indonesian Family Life Survey (IFLS) of Wave 3 and 4. This study finds that households in rural areas are the most vulnerable to natural disasters; the average asset losses and medical/funeral costs from natural disasters are roughly USD 2,190/household. Our econometric models confirm that earthquakes are the most destructive disaster to affect household welfare, whereas droughts, forest fires, floods, and other disasters appear to have only moderate effects. Earthquakes reduce households' probability of being non-poor by 5 percentage points. Disaster mitigation and preparedness play a significant role in reducing the devastating impacts of disasters and in lessening households' vulnerability to poverty. The policy recommendations resulting from this study include advancing the provision of life and health insurance, promoting food buffers, and increasing households' access to formal credit institutions.
Keywords: Q54; I31; I32; 330; natural disasters; mitigation; welfare; vulnerability; poverty; Indonesia